Multidrug resistance in tumour cells: characterisation of the multidrug resistant cell line K562-Lucena 1 - RUMJANEK,VIVIAN M. (2001)
Multidrug resistance to chemotherapy is a major obstacle in the treatment of cancer patients. The best characterised mechanism responsible for multidrug resistance involves the expression of the MDR-1 gene product, P-glycoprotein. However, the resistance process is multifactorial. Studies of multidrug resistance mechanisms have relied on the analysis of cancer cell lines that have been selected and present cross-reactivity to a broad range of anticancer agents. This work characterises a multidrug resistant cell line, originally selected for resistance to the Vinca alkaloid vincristine and derived from the human erythroleukaemia cell K562. This cell line, named Lucena 1, overexpresses P-glycoprotein and have its resistance reversed by the chemosensitisers verapamil, trifluoperazine and cyclosporins A, D and G. Furthermore, we demonstrated that methylene blue was capable of partially reversing the resistance in this cell line. On the contrary, the use of 5-fluorouracil increased the resistance of Lucena 1. In addition to chemotherapics, Lucena 1 cells were resistant to ultraviolet A radiation and hydrogen peroxide and failed to mobilise intracellular calcium when thapsigargin was used. Changes in the cytoskeleton of this cell line were also observed.